IMPACTO DE LA INDUSTRIALIZACIÓN EN EL DESEMPLEO EN 91 PAÍSES A NIVEL GLOBAL Y POR GRUPOS DE INGRESOS: UN ENFOQUE CON DATOS DE PANEL Y MODERNAS TÉCNICAS DE COINTEGRACIÓN Y CAUSALIDAD, EN EL PERIODO 1990-2016 - Acaro Veintimilla, Leidy Alejandra (2019)
The objective of this research is to determine the effect of industrialization on unemployment in 91 countries of the world, classified by levels of income in the period 1990-2016, panel data and cointegration and causality techniques have been used. For its effect, the data has been taken from the World Bank (2017). The work is based on the empirical evidence reviewed, as well as the arguments of Kaldor (1966) and the report on Industrial Development of UNIDO (2016), which states that the industrial-manufacturing sector represents a potential generator of employment, mainly due to the increase in the productivity of the sector, which represents a sufficient condition to generate a structural change in the economies and therefore reduce unemployment. The results corroborate the existence of a negative and statistically significant relationship between the variables, the higher the industrialization, the lower the unemployment. Likewise, the cointegration tests of Westerlund (2007) and Pedroni (1999) verify the existence of short and long-term equilibrium between the global variables and in all groupings of countries. Finally, the causality test of Dimietry and Hurlin (2012) shows bidirectional causality of the variables at the global level and in the PIA, and unidirectional causality in the PIMA.